2014
DOI: 10.1504/ijtmkt.2014.058080
|View full text |Cite
|
Sign up to set email alerts
|

Lead users, suppliers, and experts: the exploration and exploitation trade-off in product development

Abstract: We develop a theoretical framework that explains how lead users, key suppliers, and product experts play into the exploration and exploitation trade-off, and how their changing roles support the development of their ideas into marketable solutions. We explain that close collaboration with product experts, suppliers and lead users supports exploitation, as it tends to enable the development and improvement of existing products. Irregular or non-systematic collaboration with lead users, on the other hand, suppor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 57 publications
1
7
0
Order By: Relevance
“…Previous studies have demonstrated that supplier collaboration has a positive effect on NPD in terms of product variety (Al-Zu'bi & Tsinopoulos, 2012), product development time (Tsinopoulos & Al-Zu'bi, 2012) and NPD cost (Tsinopoulos & Al-Zu'bi, 2014). While these studies highlight the importance of supplier collaboration on NPD, they do not provide a complete picture of the effect of this partnership on innovation performance.…”
Section: Supplier Collaboration and Innovation Performancementioning
confidence: 93%
See 1 more Smart Citation
“…Previous studies have demonstrated that supplier collaboration has a positive effect on NPD in terms of product variety (Al-Zu'bi & Tsinopoulos, 2012), product development time (Tsinopoulos & Al-Zu'bi, 2012) and NPD cost (Tsinopoulos & Al-Zu'bi, 2014). While these studies highlight the importance of supplier collaboration on NPD, they do not provide a complete picture of the effect of this partnership on innovation performance.…”
Section: Supplier Collaboration and Innovation Performancementioning
confidence: 93%
“…Lead users have long been regarded as a key source of innovation (Lilien et al, 2002), and there has therefore been a focus on identifying ways in which they can be most effectively engaged in the NPD process. The demonstrated benefits of lead user collaboration in NPD include decreased cycle and product development times, lower costs, and greater product quality (Lonsdale & Newell, 1996;Hamann, 1999;Al-Zu'bi & Tsinopoulos, 2012;Tsinopoulos & Al-Zu'bi, 2014).…”
Section: Lead User Collaboration and Innovation Performancementioning
confidence: 99%
“…To reveal more rigorous results, the effects of three control variables-company size, company age, and length of relationship-are also considered. Technical knowledge capacity has the ability to encourage collaboration between suppliers and lead users, and is likely to improve the organization's innovative ability (Tsinopoulos & Al Zu'bi, 2013). The technical knowledge that suppliers may have can provide an opportunity to re-assess the potential new ideas and make the necessary improvements starting from the research and development phases and in subsequent testing and analysis phases.…”
Section: Research Frameworkmentioning
confidence: 99%
“…Such knowledge is likely to have been acquired by an iterative process that starts with the identification of lead users needs and is followed by the creative application of suppliers' technical skills. On one hand, It has been argued that while lead users and suppliers have different incentives to be involved in NPD activities, they will have analogous technical knowledge with regard to the new products under development (Tsinopoulos & Al Zu'bi, 2013 Hippel & Riggs, 1996). These authors further pointed to the fact that products suggested by lead users were found to be more attractive for consumers than other products.…”
Section: The Effect Of Lead-users Collaboration In Npd On Open Innovamentioning
confidence: 99%
“…It enables companies to be responsive to uncertainty in the amount of customer demand and preferences and to adjust volume and mix of output to meet market demand (D'souza & Williams, 2000;Gerwin, 1993). Such a capability requires the ability to introduce new or customized products (Abdallah & Matsui, 2009), provide a variety of products (Tsinopoulos & Al-Zu'bi, 2014), flexibility to change initially planned delivery dates (Abdallah et al, 2009), the ability to modify product mix effectively , and the rapidity with which companies respond to signals of environment (Zaheer & Zaheer, 1997). Heizer et al (2013) pointed to flexibility performance as the ability to develop products on time, deliver products fast, have reliable scheduling, and flexible performance.…”
Section: Flexibility Performancementioning
confidence: 99%